The m? Protocol F5 and Hamming m? Codes (London Journal of Research In Science: Natural and Formal, 2023)
The m? structure introduce pure and applied mathematics using the set FpZ = Fp ? {xpZ | e(x ? 0(mod(p)))}, p prime, to then present mathematical structures resulting from the sets originally introduced F. Ayissi Eteme [6]. This work consists in defining on FpZ the notion of Ham- ming code according to m? set structure. We show a relation between m? protocol F5 and Hamming m? code. By using this relation, we get a new steganography based on the bit modalities of a code word.
Keywords: m? set; Hamming m? codes; steganography; m? protocol F5.